2013
DOI: 10.1167/iovs.13-12084
|View full text |Cite
|
Sign up to set email alerts
|

Activated αvβ3 Integrin Regulates αvβ5 Integrin–Mediated Phagocytosis in Trabecular Meshwork Cells

Abstract: The αvβ5 integrin-FAK-mediated pathway regulates phagocytosis in TM cells and this pathway is inhibited by activation of αvβ3 integrins. This suggests that changes in integrin expression and activity may be responsible for alterations in phagocytosis observed in steroid induced glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 46 publications
7
69
0
2
Order By: Relevance
“…We also found that pre-treatment of cells with an ␣V␤5 function-blocking antibody significantly reduces phagocytosis by lens epithelial cells (Fig. 7) consistent with the established function of ␣V␤5 for phagocytosis in other tissues, including the retinal pigmented epithelium (46,(55)(56)(57) and trabecular meshwork (85). Finally, we demonstrate that exposure of lens epithelial cells to UVA light results in degradation of ␣V␤5 and reduced lens epithelial cell phagocytosis (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…We also found that pre-treatment of cells with an ␣V␤5 function-blocking antibody significantly reduces phagocytosis by lens epithelial cells (Fig. 7) consistent with the established function of ␣V␤5 for phagocytosis in other tissues, including the retinal pigmented epithelium (46,(55)(56)(57) and trabecular meshwork (85). Finally, we demonstrate that exposure of lens epithelial cells to UVA light results in degradation of ␣V␤5 and reduced lens epithelial cell phagocytosis (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…For functional follow-up, the human anterior segment perfusion model, which recapitulates outflow regulation in vivo (Johnson and Tschumper, 1987), has been employed. Many of the changes seen in the trabecular meshwork of human eyes treated with glucocorticoids are also seen in eyes perfused with glucocorticoids in vitro (Clark et al, 1995b) and can be mimicked in cultured trabecular meshwork cells (Filla et al, 2011; Gagen et al, 2014; Gagen et al, 2013). This provides evidence for a direct action of glucocorticoids on the trabecular meshwork (rather than a systemic action).…”
Section: Cell Biologymentioning
confidence: 99%
“…αVβ5 integrin is able to bind and internalize apoptotic cells via Rac1 activation [13, 14]. In trabecular meshwork cells, αVβ5 integrin mediates phagocytosis via FAK activation, while αVβ3 reduces phagocytotic activity in these cells [15]. In contrast, αVβ3 serves to internalize apoptotic neutrophils in macrophages [13].…”
Section: Introductionmentioning
confidence: 99%